Association of multimorbidity and physical activity among older adults in India: an analysis from the Longitudinal Ageing Survey of India (2017–2018) - Nandita Saikia; Bandita Boro (BMJ Open, 2022)
Objective To examine the association of multimorbidity and physical activity among older adults in India.Design A cross-sectional study was conducted using large representative survey data.Setting and participants The study used data from the nationally representative ‘Longitudinal Ageing Study in India (LASI),’ conducted during 2017–2018. The study included a total sample of 65 336 older adults aged 45 years and above in India.Methods Moderate and vigorous physical activities were measured separately by self-reported questionnaires. Physical activity was calculated as minutes of metabolic equivalent tasks per week. The outcome variable was a categorical variable where 2=the prevalence of more than one morbidity, 1=presence of one morbidity and 0=none. Bivariate analysis and multinomial logistic regression were applied to fulfil the objectives.Results 27.39% of older adults in India had multimorbidity. 31.02% of older adults did not engage in any moderate physical activities. Also, 59.39% of older adults did not engage in any vigorous physical activities. Older adults reporting low (adjusted relative risk ratio (A RRR): 1.10, 95% CI 1.03 to 1.18) and moderate (A RRR): 1.05, 95% CI 0.98 to 1.13) level of moderate physical activity were significantly more likely to suffer from multimorbidity compared with no involvement in moderate physical activity. However, older adults who reported high (A RRR: 0.79, 95% CI 0.75 to 0.84), moderate (A RRR: 0.88, 95% CI 0.80 to 0.98) and low level of vigorous physical activity (A RRR: 0.94, 95% CI 0.86 to 1.02) had significantly less multimorbidity in comparison to those who never engaged in vigorous physical activity.Conclusion Lack of physical activity is associated with multimorbidity among older adults. Physical activity promotion should be adopted as a primary strategy in reducing the burden of morbidity and multimorbidity.